2016
DOI: 10.1186/s12877-016-0211-8
|View full text |Cite
|
Sign up to set email alerts
|

Encountering aged care: a mixed methods investigation of medical students’ clinical placement experiences

Abstract: BackgroundResidential aged care is an increasingly important health setting due to population ageing and the increase in age-related conditions, such as dementia. However, medical education has limited engagement with this fast-growing sector and undergraduate training remains primarily focussed on acute presentations in hospital settings. Additionally, concerns have been raised about the adequacy of dementia-related content in undergraduate medical curricula, while research has found mixed attitudes among stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 46 publications
1
27
0
2
Order By: Relevance
“…HCP training might be challenging as residents and newly graduated family physicians report little interest in caring for seniors afflicted with complex or chronic diseases, especially in home care settings [28]. New training models, such as clinical placements in long-term care settings [29], and interprofessional faculty development programs in geriatrics [30, 31] show promise to improve the autonomy of HCP in their clinical assessment and decision-making with vulnerable older adults.…”
Section: Discussionmentioning
confidence: 99%
“…HCP training might be challenging as residents and newly graduated family physicians report little interest in caring for seniors afflicted with complex or chronic diseases, especially in home care settings [28]. New training models, such as clinical placements in long-term care settings [29], and interprofessional faculty development programs in geriatrics [30, 31] show promise to improve the autonomy of HCP in their clinical assessment and decision-making with vulnerable older adults.…”
Section: Discussionmentioning
confidence: 99%
“…One of the issues that the medical profession has to face is prioritizing elderly care, as the number of older people suffering chronic illness and multiple comorbidities is on the rise 1 . For example, in Ireland research shows that individuals aged 65 years and over make up 11.6% of the population in 2011, which is believed to reach 22% by 2041 2 , while in Australia, it is predicted that the number of individuals aged 65 years and over will increase from 13% in 2007 to 23% in 2061 1 . Aging population is on increase both in developed and developing countries 3 .…”
mentioning
confidence: 99%
“…Following the rise in life expectancy and medical advances, multi-morbidity and poly-pharmacy has increased recently; this trend has been very significant in the elderly 6 . Hence, the medical profession needs to handle these patients effectively 1,7,8 . However, research conducted in the UK shows that medical undergraduate students have not been trained for treatment of these patients sufficiently, and it was also reported that less than two weeks of a five-year educational program had been dedicated to elderly health care 1,9 .…”
mentioning
confidence: 99%
See 2 more Smart Citations